CHARACTERISTICS OF PUBLIC ROADSIDE PARKING IN SURABAYA CITY: ANALYSIS OF RETRIBUTION POTENTIAL TO INCREASE LOCAL REVENUE - Abdillah, Pradana Affan; Patriadi, Andi; Sajiyo, Sajiyo (International Journal of Social Service and Research, 2025)
The problem of public roadside parking (TJU) in Surabaya City, as one of the metropolitan cities in Indonesia, is a complex issue and requires serious attention in its management. This study aims to analyze the characteristics of TJU parking, evaluate its potential contribution to regional own-source revenue (PAD), and identify supporting and inhibiting factors in increasing parking retribution. The data obtained from the parking spot survey was comprehensively analyzed to identify parking characteristics and their effects on road sections, ultimately informing recommendations to enhance parking capacity and efficiency in the future. The results of this study provide a useful tool for policy makers to understand the distribution of parking demand across the city, leading to a clearer understanding of parking usage patterns and challenges. The presence of illegal parking, as seen in cities like Jakarta and Medan, also adds complexity to the management of the parking problem. The adoption of e-parking systems, as implemented in several other cities, can improve the efficiency of parking levy collection. Furthermore, the adoption of modern technologies has proven effective in improving parking revenue and reducing operational inefficiencies.